High prevalence of vitamin D deficiency and insufficiency in patients with manifest Huntington disease: An explorative study - Chel, Victor GM; Ooms, Marcel E; van der Bent, Jessie; Veldkamp, Fleur; Roos, Raymund AC; Achterberg, Wilco P; Lips, Paul (Dermato-endocrinology, 2013)
Vitamin D deficiency and insufficiency are common in older institutionalized people and known to be associated with muscle weakness, impaired balance and increased fall risk. Falls and balance problems are common in people with Huntington disease (HD). Despite this, the prevalence of vitamin D deficiency in patients with manifest HD has never been investigated. Serum 25(OH)D levels were measured in routinely drawn blood samples from 28 Dutch institutionalized patients with manifest Huntington disease. Mean serum 25(OH)D level was 33 nmol/l (SD 15). Twenty-five subjects (89%) were vitamin D deficient or insufficient (25(OH)D < 50 nmol/L). A positive association was found between serum 25(OH)D levels and Functional Ambulation Classification (FAC) scores (p = 0.023).